Penguatan Karakter Islami Generasi Muda melalui Program Kajian Interaktif Berbasis Multimedia di Lingkungan Dinas Pemuda, Olahraga, dan Pariwisata Kabupaten Lampung Tengah - Arizal Eka Putra; Rika Agustina; Ratna Endang Sari Pahlawan; Dela Maya Sari; Ahmad Dhani Ferdiansyah; Intannia Gracelia; Erma Mika; Eny Priana; Yendri Amanda Ramadhan (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Young generations in the digital era face serious challenges in maintaining their Islamic identity due to the rapid flow of globalization, the penetration of popular culture, and the influence of social media, which often contradict Islamic values. This condition has led some adolescents and youth to experience moral degradation, a decline in interest toward religious studies, and a tendency to be more attracted to instant entertainment content. Conventional religious studies that are monotonous are often less appealing to Millennials and Gen Z, thus requiring innovative models of religious education that are relevant, engaging, and suitable for the characteristics of the digital generation. This Community Service Program (KKN) carried the theme “Strengthening Islamic Character of Young Generations through Interactive Multimedia-Based Studies at the Youth, Sports, and Tourism Office of Central Lampung Regency.” The main objective was to improve the understanding, internalization, and practice of Islamic values through creative, participatory, and enjoyable approaches. The program was implemented over one month with eight face-to-face sessions. The methods included interactive lectures, motivational video screenings, Islamic animation, group discussions, digital quizzes, and the establishment of an online discussion group via WhatsApp to maintain continuity of learning. Evaluation was carried out through field observation, pre-test and post-test, as well as in-depth interviews with participants and partners. The results showed an increase in religious understanding from an average of 58% to 82%, with active participation reaching 87%. Moreover, a youth community named Forum Pemuda Islami Lampung Tengah (FOPILTENG) was established, which is committed to continuing monthly studies independently. Technical obstacles such as limited multimedia facilities were successfully overcome by facilitators’ creativity, including utilizing simple devices and free digital platforms. Overall, the interactive multimedia-based approach proved to be effective in enhancing learning motivation, strengthening Islamic character, and fostering togetherness among youth. This model has the potential to be replicated in other regions as a strategic effort to nurture a religious, well-characterized, and competitive young generation in facing global challenges.